RELIABILITY INDICATORS AND CONDITION MONITORING OF POWER TRANSFORMERS – CASE STUDY - REXHEPI VEZIR; NAKOV PETAR (Journal of Sustainable Energy, 2018)
Transformers are sophisticated equipment in the power system compared to other elements, and as such, they require a continuous monitoring and diagnosis for safe and reliable operation. Their importance in the functionality of the power system is multiple. Monitoring techniques are used to follow their operational work and consistency. There should be listed monitoring and testing methods, collection data, parameters, failures and outage statistics, electrical and thermal parameter status, and diagnosis for determining their operating performance. Based on case analysis according to loads of the power system, a load of transformers and network topology are discussed regarding the results. In this case, are taken into account the network topology of the Kosovo Transmission System, failure statistics, failure effects and reliability indices. The model and simulation cases are performed with the NEPLAN software. These models also illustrate the cost of a failure modes in the power transformers in the different scenarios.